(untitled) (CIPEEX, 2025)
Ineligibility, within the Brazilian electoral system, is an essential mechanism for preserving electoral morality and the legitimacy of democracy itself. Governed by Article 14, §9 of the 1988 Federal Constitution and by Complementary Law No. 64/1990, it encompasses situations in which a natural or legal person convicted in administrative proceedings may be deemed ineligible for public office. The common causes of ineligibility include criminal conviction, pending judgments, convictions for abuse of political and economic power, misuse of purpose, and corrupt practices such as those uncovered in the “Operation Car Wash” investigation. In practical terms, applying ineligibility can be burdensome and inconvenient for the Judiciary, as it often leads to excessive judicialization and legally complex cases. Furthermore, debates on the topic face criticism regarding the risk of electoral law being distorted, as well as the inefficiency of the process, which may be seen as an obstacle to the proper enforcement of ineligibility. Nonetheless, it remains a fundamental provision to ensure transparent and fair elections, as well as to safeguard ethics in politics.